Perbandingan Efektivitas Terapi Cefixime dan Azithromycin pada Pneumonia Dewasa Tahun 2023 - Aminudin, Aminudin; Nuriana; Sari, Septi (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2025)
Pneumonia is an infection that causes inflammation in the lung tissue, caused by various microorganisms, with Streptococcus pneumoniae being the primary bacterial pathogen. The aim of this study is to describe the pattern of antibiotic use and compare the effectiveness of Cefixime and Azithromycin in adult pneumonia patients at the Inpatient Installation of RSUD Pemangkat in 2023. This research employs a non-experimental observational design with a retrospective approach. A total of 76 patients were selected from 314 using purposive sampling and Slovin's formula with a 10% margin of error. Data analysis was conducted using the Independent Sample T-Test. The results revealed that 42 patients (55%) were male, while 34 patients (45%) were female. Cefixime was administered to 55% of patients, while 45% received Azithromycin. Azithromycin demonstrated greater effectiveness based on clinical indicators. Patients receiving Azithromycin had a shorter hospital stay (4.24 days), a greater reduction in body temperature (1.771ºC), and a higher increase in oxygen saturation (7.29%). Conclusion: Azithromycin is more effective than Cefixime in treating adult pneumonia patients at RSUD Pemangkat in 2023.